2023
DOI: 10.3390/su15064960
|View full text |Cite
|
Sign up to set email alerts
|

The Water–Energy–Food Nexus in European Countries: A Review and Future Perspectives

Abstract: The interaction between water, energy, and food as the water–energy–food (WEF) nexus has drawn much attention recently to solve upcoming uncertainty in food security. The aim of this study is to investigate the status of the WEF nexus in European countries. It is indicated that the largest nexus studies (among 27 European countries) have been conducted in Spain and Italy. It is confirmed that there is a large number of nexus studies in water-stressed countries while there are few studies on water-abundant coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 110 publications
(134 reference statements)
1
1
0
Order By: Relevance
“…The amount of nexus research in water-scarce countries such as Iran, South Africa, Saudi Arabia, and Lebanon was slightly high, accounting for 2.1%, 1.6%, 1.5%, and 1.5%, respectively, since the WEF nexus is identified as an alternative to managing water demand and water supply [53]. A study by [54] indicated that more nexus studies and research was conducted in water-scarce countries, similar to this result. One nexus study by [55] before the Bonne conference in 2008 was applied in water-scarce countries in Central Asia with the aim of increasing food security.…”
Section: Nexus Studies Worldwidesupporting
confidence: 53%
See 1 more Smart Citation
“…The amount of nexus research in water-scarce countries such as Iran, South Africa, Saudi Arabia, and Lebanon was slightly high, accounting for 2.1%, 1.6%, 1.5%, and 1.5%, respectively, since the WEF nexus is identified as an alternative to managing water demand and water supply [53]. A study by [54] indicated that more nexus studies and research was conducted in water-scarce countries, similar to this result. One nexus study by [55] before the Bonne conference in 2008 was applied in water-scarce countries in Central Asia with the aim of increasing food security.…”
Section: Nexus Studies Worldwidesupporting
confidence: 53%
“…For example, in Asian and African countries, more attention has been paid to crop production, crop productivity, and water availability in agricultural sectors. Differently, in European countries [54], more attention was paid to the energy sector by using renewable energy production. However, are we really sure that different continents/countries have and will have different needs?…”
Section: Discussionmentioning
confidence: 99%
“…Most nexus research has focused mainly on the water-energy-food and the waterenergy coupling. In Europe, especially in Italy and Spain, studies have largely concentrated on energy production within the water and energy pillars, as highlighted by Rezaei Kalvani and Celio [31]. On the other hand, North American research predominantly explores the food-energy-water nexus, a concept frequently discussed in that region and initiating from the food pillar.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader context, the mapping strategy and solutions presented here are of utmost importance (i) in managing and optimizing water resources abstraction for human purposes (as is evident) as well as (ii) when carrying out effective water-energy-food-land-climate nexus studies (WqEFLC nexus, sensu [62]) for sustainable development goals. For example, an effective WqEFLC nexus study must also consider the layered heterogeneity of an alluvial aquifer.…”
Section: Discussionmentioning
confidence: 99%